Development of a high-productivity grafting robot for Solanaceae - Xie, Zhongjian; Gu, Song; Chu, Qi; Li, Bo; Fan, Kaijun; Yang, Yanli; Yang, Yi; Liu, Xiaogeng (International Journal of Agricultural and Biological Engineering, 2020)
Grafting is a green, environmentally friendly, and sustainable way to prevent soil-borne diseases. Although artificial grafting is the main grafting approach used for grafting production, it has some problems which are low productivity, unstable operating quality and labor-intensive. Hence, some countries have been engaged in the development of grafting robots for the past two decades; however, the productivity of these grafting robots has no advantage when compared to artificial grafting. This study aims to develop a high-productivity grafting robot (HPR) for Solanaceae. To improve grafting productivity, this paper adopted plug trays to feed crown-removed rootstocks automatically and carried out multi-plant simultaneous grafting to improve grafting productivity and extensibility. Manipulators were employed to take out rootstocks, increase the distance between them, and transfer them to transfer cups for the simultaneous multi-plant grafting. At the same time, negative pressure mechanisms were designed for speeding up the auxiliary feeding of root-removed scions. Although the HPR was designed in a two-operator mode, a one-operator mode can also be implemented by adjusting the control program. Tests were conducted by varying the artificial feeding speed to analyze the performance of the grafting robot. The results showed that the productivity of the robot in the two-operator mode was 2250 plants/h, and 1542 plants/h in one-operator mode; comparing the artificial feeding productivity with auto grafting productivity, it was found that the capacity of the grafting robot was higher than the feeding speed of the one-operator mode but lower than that of the two-operator mode. Keywords: robotic, productivity improvement, simultaneous multi-plant grafting, negative pressure feeding DOI: 10.25165/j.ijabe.20201301.5209 Citation: Xie Z J, Gu S, Chu Q, Li B, Fan K J, Yang Y L, et al. Development of a high-productivity grafting robot for Solanaceae. Int J Agric & Biol Eng, 2020; 13(1): 82–90.